Requests for dispensation of a ratum et non consummatum marriage: Canons 1061; 1681; 1704 §1 (Roman replies and CLSA advisory opinions, 2009)
"In a memorandum to the US. Bishops dated August 3, 2009, Cardinal Francis George, O.Ml., President of the United States Conference of Catholic Bishops, forwarded a request from his Eminence Cardinal Antonio Canizares Llovera, Prefect of the Congregation for Divine Worship and the Discipline of the Sacraments, dated June 13, 2009 (Port. N. 551/09M), that the Congregation's December 20, 1986 procedures be disseminated to those competent in such matters. An English translation of the 1986 procedures can be found in Canon Law Digest Vol. 13, pages 695-701. The Congregation expressed concern that some tribunal officials, viewing the ratum process as highly specialized and complex, may be hesitant to utilize it, even in appropriate cases. To assist with the local instruction of such cases and the preparation. Of the necessary acta for submission to the Holy See, the Congregation also provided a helpful Pro Memoria."